2020
DOI: 10.3390/nano10091627
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Methods for Calculating Nano Crystal Size of Natural Hydroxyapatite Using X-Ray Diffraction

Abstract: We report on a comparison of methods based on XRD patterns for calculating crystal size. In this case, XRD peaks were extracted from hydroxyapatite obtained from cow, pig, and chicken bones. Hydroxyapatite was synthesized through the thermal treatment of natural bones at 950 °C. XRD patterns were selected by adjustment of X-Pert software for each method and for calculating the size of the crystals. Methods consisted of Scherrer (three models), Monshi–Scherrer, three models of Williamson–Hall (namely the Unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
154
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 289 publications
(160 citation statements)
references
References 41 publications
5
154
0
1
Order By: Relevance
“…In addition, crystallographic parameters ( Table S1 ) of CaTiO 3 and analyzed data by X’Pert [ 24 ] nasiri are recorded as the cell volume = 54.44 3 and crystal density = 4.14 ± 0.01 g/cm 3 , and the space group is Pm-3m. In addition, the crystal size of CaTiO 3 was calculated by the Monshi–Scherrer equation ( Figure S2 ) [ 25 ] and BET analysis. The crystal size values were registered at ~59.10 and 63.02 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, crystallographic parameters ( Table S1 ) of CaTiO 3 and analyzed data by X’Pert [ 24 ] nasiri are recorded as the cell volume = 54.44 3 and crystal density = 4.14 ± 0.01 g/cm 3 , and the space group is Pm-3m. In addition, the crystal size of CaTiO 3 was calculated by the Monshi–Scherrer equation ( Figure S2 ) [ 25 ] and BET analysis. The crystal size values were registered at ~59.10 and 63.02 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In previous research, the polymorphic rhombohedra–tetragonal phase transition temperature was found shifted toward room temperature with the Li doping for BCZT [ 26 ]. The study showed that BCZT lead-free piezoelectric ceramic with improved performance properties at room temperature can be achieved by shifting the polymorphic phase transition point nearer to room temperature through the addition of LiF [ 9 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lattice constant a can be calculated using the equation [ 9 ]: where, h , k , and l are indexes of the XRD reflection peak, and d is the interplaner spacing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations